Effects of long-term individual housing of middle-aged female Octodon degus on spatial learning and memory in the Barnes maze task - Popović, Natalija; Baño-Otalora, Beatriz; Rol, María Ángeles; Venero, César; Madrid, Juan Antonio; Popović, Miroljub (Frontiers in Behavioral Neuroscience, 2023)
Prolonged social isolation is a form of passive chronic stress that has consequences on human and animal behavior. In the present study, we investigated the effects of long-term social isolation on anxiety levels in the light-dark test, and spatial orientation abilities in the Barnes maze. Middle-aged female Octodon degus were allocated to either group-housed (3 animals per cage) or individually-housed for 5 months. Under this experimental condition, there were no significant group differences in the anxiety level tested in the light-dark test and in the motivation to escape from the Barnes maze. On the last acquisition training day of spatial learning, individually- housed animals had a significantly higher number of correct responses and a smaller number of reference and working memory errors than the group-housed animals. In addition, isolated animals showed a tendency for reference and working memory impairment on the retention trial, while group-housed degus showed improvement in these parameters. The present study indicates that prolonged social isolation during adulthood in female degus has a dual effect on spatial orientation. Specifically, it results in a significant improvement in acquisition skills but a slight impairment in memory retention.